Becoming an Eco-Innovative Industrial Cluster Through De-Regionalization: Lessons from Italian and Brazilian Clusters. Issue 1 (2nd January 2021) - Casarotto Filho, Nelson; Santa Catarina, Artur; Ferasso, Marcos; Cunha, Idaulo José
Abstract: This research intends to contribute to the literature by exploring current changes in de-regionalization of intervention forms in clusters to transform them into eco-innovative industrial clusters. The regions of Emilia-Romagna (Italy) and Santa Catarina (Brazil) are analyzed as longitudinal case studies. Our findings revealed that Emilia-Romagna industrial districts are targeting innovation and sustainability, allowing the Italian clusters to benefit from the shift from regionalized "100% made in Italy" to greater value added through innovation and "green." The Santa Catarina region is a pioneer Brazilian State in the de-regionalization of clusters through Innovation Centers and thus contrasts with the Italian region. Contributions for considering third-level government in microregions are addressed for Latin American practitioners, scholars, and decision makers.